Estimation of REV for fractured rock masses based on Geological Strength Index - Huang, Huajie; Shen, Jiayi; Chen, Qiushi; Karakus, Murat (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2020)
The representative elementary volume (REV) of fractured rock masses is a significant index to investigate the rock mass behaviors in the continuum mechanics. In this research, a new indicator to estimate the REV size of fractured rock masses based on the Geological Strength Index (GSI) is proposed. For this purpose, a new method that combines the PFC-based synthetic rock mass (SRM) model with the Hoek-Brown (HB) failure criterion is proposed to investigate the strength and deformation properties of fractured rock masses under biaxial stress conditions. Extensive numerical analyses are carried out to estimate variation of the uniaxial compression strength (UCS), deformation modulus (E) and GSI of the Brunswick mine rock mass with increasing the size of the SRM models up to a REV size. Results show that the GSI-based indicator gives relatively larger REV size compared with the traditional UCS or deformation modulus (E) based indicators. Compared with the traditional indicators, the proposed GSI-based indicator has merits of not only reflecting the geometrical characteristics of rock structures but also containing both geometrical and mechanical properties of discontinuities.